The Influence of the Hawrami Dialect on Mawlawi Tawagozi’s Poems - Wali, Awat Hassan; Mohammed Salih, Hemn Karim; Aziz, Salm Hassan; Hama Ali, Aso Ahmed; Abdulla, Shwana Noori (Journal of Linguistics and Social Sciences, 2023)
The Goran dialect is crucial to our literary history as the Kurdish nation. It has also remarkably impacted the works of some famous authors and poets of our Kurdish nation. Mawlawi Tawagozi wrote his poems (Poetry) in Hawrami, a branch of the Gorani dialect. In the present study, the questions regarding the factors that have driven this Sorani dialect poet to adopt Hawrami in writing his poetry have been answered. Moreover, according to the scientific sources as well as analyzing his poems, the prominent factors which resulted in the supremacy of the Hawrami dialect in the poetry of the poet mentioned above are explained. In the practical part of this study, the factors that fascinate this poet with the Hawrami dialect are described and exemplified. The following questions in this study are answered: Why has this dialect been so significant, and has this poet written his entire poetry in it? Was it his love for that dialect, the beauty and charm of the Hawraman area and the love for Naqshabandi Sufism, or maybe due to his love for Tawela and Byara religiously It was Islam Sheiks? Did the ruling and policy of the Ardalan Emirate (Vassaldom) have any role?.